2015
DOI: 10.1016/j.ijscr.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of left sided acute appendicitis in elderly male with asymptomatic midgut malrotation

Abstract: HighlightsMidgut malrotation in adulthood is rare, with reported incidence 0.1–0.5%.Acute appendicitis with undiagnosed midgut malrotation has been sparsely described.Presenting symptoms are often atypical which delay diagnosis.Early recognition with appropriate imaging is key to diagnosis and appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
8
0
4
Order By: Relevance
“…Embryologiquement, la première rotation se déroule avant la 10 ème semaine de gestation lorsque l’intestin primitif est encore situé hors de l’abdomen. Cette rotation place la portion prévitelline (grêle) à droite et la portion post vitelline (colon) à gauche; un arrêt à ce stade est à l’origine du mésentère commun complet [ 8 ]. Le mésentère commun complet résulte alors d’un arrêt de la rotation intestinale à 90°.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Embryologiquement, la première rotation se déroule avant la 10 ème semaine de gestation lorsque l’intestin primitif est encore situé hors de l’abdomen. Cette rotation place la portion prévitelline (grêle) à droite et la portion post vitelline (colon) à gauche; un arrêt à ce stade est à l’origine du mésentère commun complet [ 8 ]. Le mésentère commun complet résulte alors d’un arrêt de la rotation intestinale à 90°.…”
Section: Discussionunclassified
“…Les malformations intestinales demeurent très souvent asymptomatiques et donc non diagnostiquées à l’âge adulte [ 8 ]. A cet âge, le mésentère commun complet est souvent découvert, soit fortuitement, soit dans le cadre d’une pathologie tumorale ou inflammatoire du tube digestif, notamment d'une appendicite ectopique dont le diagnostic clinique a souvent erré voir été non évoqué [ 4 , 5 , 7 , 8 ].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Singla et al [103] reported a case of left-sided acute appendicitis in an elderly male with asymptomatic midgut rotation. Their conclusion was that imaging offers significant advantage for timely and definitive management.…”
Section: Left-sided Appendicitismentioning
confidence: 99%